2013
DOI: 10.1007/s00405-013-2359-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends in intraoperative neural monitoring for thyroid and parathyroid surgery amongst otolaryngologists and general surgeons

Abstract: The role of intraoperative neural monitoring (IONM) in thyroid and parathyroid surgery remains a controversial subject for surgeons regardless of surgical training and background. This study aims to compare usage patterns and motivations behind IONM among otolaryngologist-head and neck surgeons (OTO-HNS) and general surgeons (GS) performing thyroid and parathyroid surgery. The study is a multi-institution survey of 103 otolaryngology and affiliated 103 GS programs in the US. 206 surveys were sent to OTO-HNS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 9 publications
0
43
0
Order By: Relevance
“…Many studies reported a high negative predictive value of 92-100% but a low and highly variable positive predictive value of 10-90% [2,32]. Recurrent laryngeal nerve monitoring is being used with increasing frequency in the United States during thyroidectomy, partly driven by the medico-legal system [10,22,33-35] while German surgeons use the method routinely even much more often than the Americans [1]; the rates of the use of neuromonitoring have recently become almost equivalent between general surgery- and otolaryngology-trained surgeons [14,22,36]. However, the use of recurrent laryngeal nerve monitoring is associated with increased time of setup and increased cost of equipment by about 5-7% [1,33].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported a high negative predictive value of 92-100% but a low and highly variable positive predictive value of 10-90% [2,32]. Recurrent laryngeal nerve monitoring is being used with increasing frequency in the United States during thyroidectomy, partly driven by the medico-legal system [10,22,33-35] while German surgeons use the method routinely even much more often than the Americans [1]; the rates of the use of neuromonitoring have recently become almost equivalent between general surgery- and otolaryngology-trained surgeons [14,22,36]. However, the use of recurrent laryngeal nerve monitoring is associated with increased time of setup and increased cost of equipment by about 5-7% [1,33].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the RLN enters the larynx at precisely the origin of KJD: through the Killian-Jamieson triangle. 12,13 The use of a nerve monitor does not replace a surgeon's knowledge of head and neck anatomy, and during routine open ZD operations, the surgeon must be able to recognize the RLN if encountered. This is because the origin of ZD, Killian's dehiscence is located posteriorly, while the RLN enters the larynx laterally.…”
Section: Discussionmentioning
confidence: 99%
“…To remedy this deficiency, active efforts are being made to launch a series of training courses emphasizing the need to use intermittent IONM and continuous IONM (CIONM) in a standard fashion (1).…”
Section: The Ionm Formula Standard: Room For Improvementmentioning
confidence: 99%
“…There are no corresponding data for CIONM, which may have been used in 2015 on almost 10% of all thyroid operations in Germany based on personal information (unpublished data). In the United States, the rationale for using IONM is split along professional lines: general surgeons prefer IONM to locate the RLN, whereas otolaryngologists use IONM more often for monitoring the RLN during thyroid resection and for documentation purposes to guard against malpractice claims (1).…”
Section: Challenges Of Implementation and Technological Pitfalls Of Ionmmentioning
confidence: 99%